Tungstato de prata como aditivo para tintas imobiliárias: estudo de propriedades e potencial de uso - Costa, Robledo Cássio da (2025)
This study presents a bibliometric, patentometric, and experimental analysis of the application of silver tungstate (Ag₂WO₄) as an antimicrobial additive in architectural paints. The research mapped the scientific and technological production, identifying key trends, collaboration networks, and areas of greatest impact. The methodology included data collection from indexed databases such as Web of Science and Scopus, as well as the experimental synthesis of silver tungstate in its alpha, beta, and gamma phases through chemical precipitation. The samples were characterized using Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), and Thermal Analysis (TGA). The results revealed that the beta phase exhibited lower crystallinity and greater morphological irregularity, characteristics that correlated with the best antimicrobial activity, with a Minimum Inhibitory Concentration (MIC) of 16 μg/mL against Escherichia coli. In contrast, the gamma and alpha phases showed higher structural organization but reduced antimicrobial activity. The bibliometric analysis indicated significant growth in research on biocides for paints over the past 10 years. The patentometric analysis revealed an increase in patent filings related to biocidal paints, suggesting the feasibility of transferring academic knowledge to the industrial sector. Tests with acrylic paint coatings demonstrated color changes, possibly due to interactions between the nanoparticles and the polymer matrix. In conclusion, silver tungstate, particularly in the beta phase, proved to be a promising antimicrobial additive, though challenges remain regarding phase stability and visual (aesthetic) impact. This research contributes to the development of functional coatings aligned with sustainability and safety demands in the construction industry.